Geuchiek's Role in Lhok Cut Village, Sawang District in Empowering Non-Formal Education: A Qualitative Research - Zakiah (Jurnal Profesi Guru Indonesia, 2024)
The Role of Geuchiek in Lhok Cut Village, Sawang Subdistrict in Empowering Non-Formal Education. The background of this problem is the lack of Geuchiek's role in empowering non-formal education in Lhok Cut Village, Kec. Sawang. The problem discussed is how the role of geuchiek in the implementation of education, the role of geuchiek in the responsibility of community education, and the obstacles faced by geuchiek in. empowering non-formal education in the village of Lhok Cut District. Sawang. The purpose of the discussion is to find out the role of geuchiek in the implementation of education, the role of geuchiek in the responsibility of community education, and the obstacles faced by geuchiek in the empowerment of non-formal education in the village of Lhok Cut District. Sawang. While collecting data, the writer did library research and by jumping directly into the field (field research). The research object is Geuchiek gampong and the leader of the non-formal education board in Lhok Cut Village. With the method as explained above, it was concluded that the role of geuchiek in the implementation of education in the village of Lhok Cut District. Sawang is very important in empowering community education. This is done by Geuchiek Gampong Lhok Cut to improve the progress of education in his village, so that Geuchiek always participate in every educational activity in the community. The role of geuchiek in the responsibility of community education in the village of Lhok Cut District. Sawang is a geuchiek who is also responsible for the continuity of education in his village. Therefore, all educational activities held in the village must be as geuchiek knowledge. Obstacles faced by geuchiek in empowering non-formal education in Lhok Cut Village, Kec. Sawang is the lack of village income so that the geuchiek is unable to finance and pay attention to non-formal education activities in the village, so non-formal education will not run smoothly.